2017
DOI: 10.1016/j.brainres.2016.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of VPAC1 activation in nucleus ambiguus neurons

Abstract: The pituitary adenylyl cyclase-activating polypeptide (PACAP) and its G protein-coupled receptors, PAC1, VPAC1 and VPAC2 form a system involved in a variety of biological processes. Although some sympathetic stimulatory effects of this system have been reported, its central cardiovascular regulatory properties are poorly characterized. VPAC1 receptors are expressed in the nucleus ambiguus (nAmb), a key center controlling cardiac parasympathetic tone. In this study, we report that selective VPAC1 activation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Cardiac-projecting neurons of the nucleus ambiguus play a critical role in cardiac parasympathetic tone. Their activation elicits bradycardia via acetylcholine release in cardiac ganglia 18 . In addition, a recent study has shown that neurons in the nucleus of the solitary tract are essential for the processing and coordinating respiratory and sympathetic responses to hypoxia 19 .…”
mentioning
confidence: 99%
“…Cardiac-projecting neurons of the nucleus ambiguus play a critical role in cardiac parasympathetic tone. Their activation elicits bradycardia via acetylcholine release in cardiac ganglia 18 . In addition, a recent study has shown that neurons in the nucleus of the solitary tract are essential for the processing and coordinating respiratory and sympathetic responses to hypoxia 19 .…”
mentioning
confidence: 99%
“…Therefore, their activation elicits bradycardia via acetylcholine release in cardiac ganglia. [ 12 ] Additionally, neurons in the nucleus of the solitary tract are essential for processing and coordinating respiratory and sympathetic responses to hypoxia. [ 13 ] These studies indicate that pathological changes in the circulatory and respiratory centers in the medulla oblongata, as observed in the present case, may be strongly associated with the prognosis of acute benzyl alcohol intoxication.…”
Section: Discussionmentioning
confidence: 99%
“…The examination of the synovial fluid may reveal mild inflammation, including an increase in the total number of leukocytes with levels ≤20,000/mm 3 , 40-50% of which being polymorphonuclear (42). Also, neuropeptides such as vasoactive intestinal peptide were found in the synovial fluid of PMR patients which may contribute to the immunomodulation of synovial fluid inflammation, but also extraarticular manifestations such as cardiac rhythm dysregulations (43,44).…”
Section: Laboratory Featuresmentioning
confidence: 99%